Collaboration through superposition: How the IT artifact as an object of collaboration affords technical interdependence without organizational interdependence - James Howison; Kevin Crowston (MIS Quarterly, 2014)
This paper develops a theory of collaboration through superposition: the process of depositing separate layers on top of each other over time. The theory is developed in a study of development of community-based Free and Open Source Software (FLOSS), through a research arc of discovery (participant observation), replication (two archival case studies) and formalization (a model of developer choices). The theory explains two key findings: 1) the overwhelming majority of work is accomplished with only a single programmer working on a task and 2) when tasks appear too large for an individual they are more likely to be deferred until they are easier, rather than being undertaken through structured teamwork. It is theorized that this way of organizing is key to successful open collaboration where the IT artifact is the object of collaboration, because it allows the co-production of technically interdependent artifacts through motivationally interdependent work. The affordances of software as an object of collaboration are used as a framework to analyze efforts to learn from FLOSS in other domains of work and in the IS function of for-profit organizations.